THE PORTRAYAL OF DESIGNING AND IMPLEMENTING LEARNING TASKS BASED ON THE STUDENT'S LEARNING STYLETHE PORTRAYAL OF DESIGNING AND IMPLEMENTING LEARNING TASKS BASED ON THE STUDENT'S LEARNING STYLE - Vanny Handayani, - (2008)
The title of this study is "The Portrayal of Designing and Implementing Learning Tasks based on the Students' Learning Styles (a descriptive study of three English teachers and 11th grade students at SMA Plus Muthahhari Bandung). The study investigated the designing and implementing the learning tasks, the problems encountered by the teachers in designing and implementing the learning tasks, and the students' responses toward the learning tasks. The study was conducted at SMA Plus Muthahhari involving three English teachers and twenty-five of 11th grade students. This study was a qualitative research conducted by means of descriptive method that employed three instruments in collecting the data, which were interview, class observation, and questionnaires. The results of the study showed that teachers had a clear understanding in designing and implementing the learning tasks based on the students' learning styles. Teachers perceived that understanding the students' different learning styles influenced the teaching and learning process i.e. teachers understood better how the students learned on the basis of their learning styles, they were more motivated in planning the effective lessons, and they could get positive feedbacks from the students if the learning tasks designs were matched to students' learning styles. However, teachers found some barriers dealing with the learning tasks design that sometimes could not entirely accommodate the students' learning styles; teachers should have extra work in the preparation including planning the lessons; and the technical problems such as the use of multimedia, the books, and the students' noise. Meanwhile, the students responded positively toward the learning tasks that were designed to accommodate their learning styles i.e. students showed their enthusiasm during the activities. Based on the results of the study, it is suggested to English teachers in Indonesia that the students' different learning styles become one of the considerations in designing and implementing the learning tasks in the classroom.